Cuso4‐amine redox‐initiated radical polymerization of methyl methacrylate mediated by a CuCl2 complex: Homogeneous reverse ATRP. Issue 18 (16th June 2014) - Gao, Jie; Song, Wan; Wang, Peng; Zhai, Guangqun
ABSTRACT Kinetic results of CuSO4/2, 2'‐bipyridine(bPy)‐amine redox initiated radical polymerization of methyl methacrylate (MMA) at 70 to 90 °C in dimethylsulfoxide suggest that such initiation is characteristic of a slow rate and a low initiator efficiency, but tertiary amines exhibit a relatively higher rate. UV‐Vis spectroscopy confirms the alpha‐amino functionality of PMMA chains. CuCl2/bPy successfully mediates the redox‐initiated radical polymerization of MMA with aliphatic tertiary amines in a fashion of slow‐initiated reverse atom transfer radical polymerization (ATRP), i.e. both the initiator efficiency of aliphatic tertiary amines and the average molecular weight of PMMA increase gradually, while the molecular weight distribution remains narrow but become broader with the conversions. As the PMMA chains contain alpha amino and omega C‐Cl moieties, UV‐induced benzophenone‐initiated radical polymerization and CuICl/bPy‐catalyzed ATRP initiated from PMMA lead to block copolymers from terminal functionalities. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2562‐2578